Muscular static strength test performance: Comparison between normotensive and hypertensive workers - Cavazzotto, Timothy Gustavo; Tratis, Luriam; Ferreira, Sandra Aires; Fernandes, Rômulo Araújo [UNESP]; Queiroga, Marcos Roberto (Elsevier, 2012)
Objective: The aim of the study was to compare static muscular strength test performance between hypertensive and normotensive workers, considering the hypothesis that hypertensive individuals have lower strength than normotensive individuals. Methods: The participants consisted of 354 workers (246 men and 108 women) who underwent height, body mass, waist circumference, systolic and diastolic blood pressure (BP) measurements, as well as right and left handgrip, and scapular and lumbar strength tests. Assessments were performed during three days in all three shifts, with workers from a candy and sweets factory located in Rio Claro, in the state of São Paulo, Brazil. BP measurements were performed with a 10-minute interval, with the subject in the sitting position. Before the strength tests were performed, the workers were familiarized with the equipment; the highest value was recorded after two attempts at each test. Results: The results showed significant differences between hypertensive and normotensive individuals for age, body mass, body mass index, and waist circumference greater for hypertensive individuals. Regarding static muscle strength tests performance, the hypertensive individuals did not differ significantly from normotensive individuals; however, this difference was observed when groups divided by body mass index (BMI) were compared. The obesity group had strength values above those of the normal weight/overweight group among normotensive individuals, but this was not observed among the hypertensive individuals. As for the intragender comparison, there were no significant differences for the strength tests. Conclusion: Normotensive and hypertensive workers showed no significant differences in the performance of static muscular strength tests; however, body mass and gender seem to affect the association between muscle strength and blood pressure. © 2012 Elsevier Editora Ltda. All rights reserved.
Desempenho em testes de força estática: Comparação entre trabalhadores hipertensos e normotensos
Keywords: Health; Hypertension; Muscle strength